Climate change stressors cause metabolic depression in the blue mussel, Mytilus edulis, from the Gulf of Maine. (19th May 2016) - Lesser, Michael P.
Abstract: The interactive effects of multiple stressors associated with global climate change will expose marine organisms to physiological challenges potentially exceeding their current abilities to acclimatize. As a result the ecological effects of the rapidly increasing magnitude, and variability, of environmental change combined with the unknown physiological capacity to acclimatize (= phenotypic plasticity) or genetically adapt, remains uncertain for many marine organisms. In the Gulf of Maine (GOM), the rocky intertidal harbors the blue mussel, Mytilus edulis, an important ecosystem engineer in these communities. Using mussel collections in the Southwest GOM from different tidal heights and a common garden experiment, mussels show significant, phenotypically plastic, effects of tidal height in multiple parameters related to metabolic capacity and stress tolerance. When these mussels are then experimentally exposed to the independent and interactive effects of thermal stress and ocean acidification, several biomarkers of stress (e.g., oxidative stress, HSP70, protein synthesis) are elevated in treatments with higher temperatures, but when combined with lower pH consistent with future predictions these markers show evidence of metabolic depression. In marine ecosystems, exposure to ocean acidification has been hypothesized as a factor that would narrow the thermal window of physiological tolerance for many invertebrates such as marine mussels. The data presented here provide evidence supporting that hypothesis in blue mussels from the GOM, an ecosystem facing one of the greatest rates of change in the marine environment.